Halal source of medication; glycosaminoglycan based medicinal plantc - Che Nur Mazadillina, Zahari; Nina Suhaity, Azmi (Research India Publications, 2016)
Orthosiphon stamineus, is a herbal plant traditionally used in various types of illnesses for example to treat kidney problems, diabetes, rheumatoid, nephritis, muscle pain and also wound healing. These properties majorly attributed by phenolic compounds according to previous researchers.Throughout this study, another novel compound that is glycosaminoglycans (GAGs) were discovered from this magical plant. The best part of this finding is that, the source is halal which until now none studies upon medicinal plant were carried for GAGs activity. Additionally, the particular GAGs are facing limitation for their source leaving mostly come from non-halal source. Objective: This study is endeavouring to extract GAGs from O. stamineus plant using an optimized extraction method. Second objective is to characterize the targeted compound chemical structures. Results: Both FTIR and NMR analysis showed presence of GAGs structure. Total sulfated GAGs were found to be 106.62 mg/g surpassing several other sources of GAGs. In extraction method, this study able to increase its yield up to 47.93% proving the promising yield of this plant as new source. Conclusion: It can be concluded that O. stamineus could be the next GAGs contributor, preparing for a recent halal medication.